Infections of Chlamydia trachomatis and Mycoplasma hominis as Risk Factors for Abnormal Cervical Cells - Mardhia, Mardhia; Effiana, Effiana; Irsan, Abror; Natalia, Diana; Rahmayanti, Sari; Indarti, Junita; Rachmadi, Lisnawati; Yasmon, Andi (UI Scholars Hub, 2018)
Background: Cervical cancer is the fourth most common cancer among women across the world. Recent studies have shown that cervical cancer is not only caused by persistent infection of human papillomavirus (HPV), but sexually transmitted infections (STIs) also play a role in the pathogenesis of abnormal cervical cells. STIs frequently occur with no specific symptoms, such as the infections caused by Chlamydia trachomatis and Mycoplasma hominis. Asymptomatic STIs could lead to persistent infection. Persistent infections caused by STIs have been hypothesised to increase the access of HPV into the deeper cervical tissue and cause cervical cell abnormalities. Therefore, we conducted this study to assess the association between C. trachomatis and M. hominis infections and abnormal cervical cells. Methods: A cross-sectional study was performed on 58 outpatients at the Department of Obstetrics and Gynecology, Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Abnormal cervical cells were detected by a liquid-based cytology Pap smear, and bacterial identification was done by conducting conventional duplex polymerase chain reaction (PCR). Results: 58 patients, 14 (24.1%) showed abnormal cervical cells, whereas 44 (75.9%) patients showed normal cervical cells. The conventional duplex PCR demonstrated a positive result for C. trachomatis and M. hominis bacterial infections in only 1 (7.1%) and 2 (14.3%) patients with abnormal cervical cells, respectively. The statistical analysis revealed no significant association between the bacterial infections and the abnormal cervical cytology in the patients (p > 0.05). Conclusions: Infections caused by C. trachomatis and/or M. hominis were not associated with abnormal cervical cells.